A solid‐phase transfection platform for arrayed CRISPR screens. Issue 6 (5th June 2020) - Serçin, Özdemirhan; Reither, Sabine; Roidos, Paris; Ballin, Nadja; Palikyras, Spyridon; Baginska, Anna; Rein, Katrin; Llamazares, Maria; Halavatyi, Aliaksandr; Winter, Hauke; Muley, Thomas; Jurkowska, Renata Z; et al.
Abstract :